Color Determination from a Single Broadband Organic Photodiode. Issue 7 (9th February 2020) - Dyson, Matthew J.; Verhage, Michael; Ma, Xiao; Simone, Giulio; Tordera, Daniel; Janssen, René A. J.; Gelinck, Gerwin H.
Abstract: Establishing the color of incident light is essential for many applications, such as machine vision, but generally requires either a dispersive component or multiple spectrally selective photodetectors. In contrast, here an incident spectrum is parametrized using a single broadband organic photodiode (OPD). This is achieved by exploiting the incident wavelength dependence of charge extraction caused by optically induced trap states in a metal oxide electron extraction layer, which results in an atypical spectral dependence of the reverse bias photocurrent density vs voltage ( J–V ) characteristics. Such dependence is augmented by confining the active layer within an optical microcavity to influence the light absorption profile and thus metal oxide trap state density. The average wavelength of an (approximately normally distributed) incident spectrum is then calculated to within ≈5 nm by algorithmically minimizing the difference between a measured J–V curve and one determined from the overlap integral of a trial spectrum with previously acquired voltage bias dependent external quantum efficiency (EQE) spectra. Abstract : Color is determined using a single broadband organic photodiode by exploiting wavelength dependence in its current density versus voltage (J–V) characteristics, attributed to light‐induced trap states within a metal oxide electron extraction layer. A hypothetical incident spectrum is spectrally located by matching a J–V curve calculated from its bias‐dependent external quantum efficiency overlap integrals with a curve measured under illumination.